Pengaruh Rasio Profitabilitas Terhadap Harga Saham Sub-Sektor Farmasi Di BEI Tahun 2012-2021 - Alya Hasanah Kurniawati; Immas Nurhayati; Titing Suharti (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The purpose of this study was determine the effect of ROA, NPM,and EPS on stock prices in the pharmaceutical sub-sector in 2012-2021. This type of research data uses quantitative data using secondary data, data collection methods using literature studies, journals, and documentation. The object of this research is PT. Darya-Varia LaboratoriaT bk (DVLA), PT. Kimia Farma Tbk (KAEF), PT. Kalbe Farma Tbk (KLBF), PT. Pyridam Farma Tbk (PYFA), PT. Tempo Scan Pasific (TSPC), PT. Indofarma Tbk (INAF), and PT. Merck Tbk (MERK). The financial ratios used in this study are Return On Asset (ROA), Net Profit Margin (NPM), and Earning Per Share (EPS). The results show that partially ROA,NPM, and EPS have no significant effect on stock prices. Simultaneously shows that ROA (X1), NPM (X2), and EPS (X3) variables have a significant effect on stock prices (Y).